Glibenclamide alters interleukin-8 and interleukin-1β of primary human monocytes from diabetes patients against Mycobacterium tuberculosis infection. (July 2020) - Kewcharoenwong, Chidchamai; Saenwongsa, Wipawee; Willcocks, Samuel J.; Bancroft, Gregory J.; Fletcher, Helen A.; Lertmemongkolchai, Ganjana
Abstract: Type 2 diabetes mellitus (T2DM) is an important risk factor for development of tuberculosis (TB). Our previous study showed glibenclamide, an anti-diabetic drug used to control blood glucose concentration, reduced interleukin (IL)-8 secretion from primary human monocytes challenged with M. tuberculosis (Mtb). In mice infected with Mtb, IL-1β is essential for host resistance through the enhancement of cyclooxygenase that limits excessive Type I interferon (IFN) production and fosters Mtb containment. We hypothesize that glibenclamide may also interfere with monocyte mediated immune responses against Mtb and alter the balance between IL-1β and IFNα-mediated immunity. Purified monocytes from non-diabetic and diabetic individuals were infected with Mtb or M. bovis BCG. We demonstrate that monocytes from diabetes patients who were being treated with glibenclamide showed reduced IL-1β and IL-8 secretion when exposed to Mtb. Additionally, these responses also occurred when monocytes from non-diabetic individuals were pre-treated with glibenclamide in vitro . Moreover, this pre-treatment enhanced IFNa1 expression but was not involved with prostaglandin E2 (PGE2) expression in response to Mtb infection. Taken together, our data show that glibenclamide might exacerbate susceptibility of diabetes patients to Mtb infection by reducing IL-1β and IL-8 production by monocytes.